Review of oesophageal atresia and tracheoesophageal fistula in hospital sultanah bahiyah, alor star 2000 - 2009 - Narasimman , Sathiamurthy (2010)
Esophageal atresia (EA) and tracheoesophageal fistula (TEF) are one of the congenital anomaly occurring in the newborns with the incidence of 1 in 2500 births seen worldwide. There were 47 patients with esophageal atresia admitted to HSB from January 2000 to December 2009, out of which 26 (55%) were males and 21 (45%) females. The distribution of patients by race were 34 Malays (72%), 9 Chinese (19%) and 4 Indians (9%). Out of 47 babies with TEF and EA, 36% of them had polyhdromnios in the antenatal evaluation. There were only 3 types of EA/TEF seen; Type A (9%), Type C (87%) and Type E (4%). The birth weight of the babies range from 0.8 kg to 4.0 kg. The smallest surviving baby weighing 1.1 kg. There was a significant association with the outcome of the surgery (p< 0.05). Most of the babies (20) were operated within 24 hours of presentation. There were no significant association between time of surgical intervention and outcome (p>0.05). 23 (49%) of them were born with congenital malformation and there was a significant association with the outcome of the surgery (p<0.05). Based on the chest roentgenogram, 20 (43%) of them had pneumonia with significant association with the outcome (p<0.05). The mortality rate is 23% and the causes of death were severe pneumonia (36%), severe renal failure (18%), severe cardiac malformation (18%) and multiple congenital malformations (28%). Bremen classification is most suitable in determining the prognosis of the babies with TEF and EA in Hospital Sultanah Bahiyah, Alor Star. In conclusion, the outcome of EA and TEF is determined mainly by birth weight, congenital malformations and presence of preoperative pneumonia.